Social Dialogue (Luxembourg, 2012)
"The Social Europe guide is a bi-annual publication aimed at providing an interested but not necessarily specialised audience with a concise overview of specific areas of EU policy in the field of employment, social affairs and inclusion. It illustrates the key issues and challenges,, explains policy actions and instruments at EU level and provides examples of best practices from EU Member States. It also presents views on the subject from the Council Presidency and the European Parliament. The second volume in this series describes the history, workings and accomplishments of social dialogue at EU level. Negotiations, consultations and exchanges of information among organisations representing employers and workers (the social partners) and public authorities are an essential element of the European social model and play a key role in defining and implementing EU economic, employment and social policy as well as sectoral policies. The volume also looks at how social dialogue has evolved at the level of individual Member States in response to the economic crisis."